Improved removal of volatile organic compounds for laser‐based spectroscopy of water isotopes. (9th February 2016) - Chang, Elliot; Wolf, Adam; Gerlein‐Safdi, Cynthia; Caylor, Kelly K.
Abstract : Rationale: Volatile organic compounds (VOCs) such as methanol and ethanol in water extracted from plants cause spectral interference in isotope ratio infrared spectroscopy (IRIS). This contamination degrades the accuracy of measurements, limiting the use of IRIS. In response, this study presents a new decontamination method of VOCs for enhanced IRIS measurements. Methods: The isotopic compositions of water from laboratory‐made and field‐collected plant samples pre‐ and post‐treatment were analyzed using IRIS. Traditional treatment methods of activated charcoal and commercial pre‐combustion systems (MCM) were compared with our new treatment method that implements solid‐phase extraction (SPE). The absolute concentrations of contaminants pre‐ and post‐treatment were determined using 1 H and 13 C nuclear magnetic resonance to assess the effectiveness of the different treatments. Results: SPE removes an average of 86.7% and 78.8% ethanol and methanol, respectively, significantly reducing spectral interference. SPE reduces errors to within instrumental noise for both ethanol and methanol at concentrations found in nature (<3.0% and 0.08%, respectively). Activated charcoal minimally affected alcohol concentrations. MCM significantly worsened ethanol‐contaminated water isotope measurements by producing primary alcohol oxidation products such as formic acid, another compound that interferes with IRIS absorption. Conclusions: SPE is an effective, low‐cost method for eliminating errors in ethanol‐contaminated samples. For samples where methanol is prevalent, combining SPE and MCM is more effective than the use of SPE alone. Hence, SPE treatment alone or in conjunction with MCM is recommended as an effective pre‐analysis purification method for water extracted from plants. Copyright © 2016 John Wiley & Sons, Ltd.